Bioresorbable vascular scaffold to treat in‐stent restenosis: Single‐center experience. (7th August 2017) - Picard, Fabien; Avram, Robert; Marquis‐Gravel, Guillaume; Tadros, Victor‐Xavier; Ly, Hung Q.; de Hemptinne, Quentin; Dorval, Jean‐François; L'allier, Philippe L.; Tanguay, Jean‐François
Abstract : Aims: The management of patients with in‐stent restenosis (ISR) is still a major clinical challenge even in the era of drug‐eluting stents (DES). Recent studies have demonstrated acceptable clinical outcomes for the everolimus‐eluting bioresorbable vascular scaffold (BVS) ABSORB™ in patients with stable coronary artery disease but data are scarce on its use in patients with ISR. We report the long‐term results of our preliminary experience with this novel approach at our institution. Methods and Results: We investigated the safety and efficacy of BVS implantation to treat ISR. 34 consecutive patients (37 lesions) underwent PCI for ISR with BVS implantation between May 2013 and June 2015 at our institution and were included in the current analysis. Follow‐up was available in 91.9% of the patients. Mean follow‐up period was 801.9 ± 179 days. One patient had definite scaffold thrombosis (ScT) 2 months after stent implantation which was treated with DES. Five patients (six lesions) experienced target lesion revascularization (TLR). The composite endpoint rate of TLR, ScT, myocardial infarction, and death occured in 6/37 lesions at follow‐up (16.2%). Conclusions: These real‐world data using BVS in patients with ISR demonstrates that ISR treatment with ABSORB™ BVS is feasible but could have slightly higher target lesion failure rates as compared to DES. This proof of concept could be hypothesis‐generating for larger randomized controlled studies.